2009
DOI: 10.1002/smj.744
|View full text |Cite
|
Sign up to set email alerts
|

From crisis to opportunity: environmental jolt, corporate acquisitions, and firm performance

Abstract: This study incorporates the external environmental context into the study of corporate acquisitions by examining the performance implications of corporate acquisitions during an environmental jolt that alters the levels of environmental munificence. We posit that compared to the periods before and after an environmental jolt, corporate acquisitions during a jolt would be positively related to firm performance. Furthermore, we suggest that organizational slack would improve firm performance and accentuate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
263
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(278 citation statements)
references
References 38 publications
4
263
0
11
Order By: Relevance
“…Also, recent studies have shown that the turbulences in the business environment can have a significant impact on bidder's returns (Beltratti & Paladino, 2013;Rao-Nicholson & Salaber, 2014a, 2014b, 2015Wan & Yiu, 2009). Thus, it is interesting to look at the impact of the 2007-2008 financial crisis on the OP of M&As in ASEAN.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, recent studies have shown that the turbulences in the business environment can have a significant impact on bidder's returns (Beltratti & Paladino, 2013;Rao-Nicholson & Salaber, 2014a, 2014b, 2015Wan & Yiu, 2009). Thus, it is interesting to look at the impact of the 2007-2008 financial crisis on the OP of M&As in ASEAN.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Thus, it is interesting to look at the impact of the 2007-2008 financial crisis on the OP of M&As in ASEAN. Though, typically, a financial crisis can have a negative effect on the company's profits, authors have also recognized good M&A opportunities that present themselves in such an environment which can lead to improvement in profitability (Krugman, 2000;Mody & Negishi, 2000;Wan & Yiu, 2009). For example, during an economic slump, firms are able to acquire targets at a lower price due to adverse economic conditions.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ndofor, Venenvenhoben and Barker (2013) found that turnaround is positively influenced by new products, acquisitions and strategic alliances. Other studies have shown the beneficial role of resources slack to reverse decline situations (Greve, 2011;Wan & Yiu, 2009). Complementary viewpoints can be given regarding threat-rigidity (Staw et al, 1981), the effects of denial (Tedlow, 2012), and inability to develop industry foresight (Prahalad & Hamel, 1990), which are not directly linked to the traditional approaches of growth and success.…”
Section: Challenges To Overcome When Conducting Research On Decline Amentioning
confidence: 98%